2022
DOI: 10.1016/j.eurox.2021.100139
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery embolization or myomectomy for women with uterine fibroids: Four-year follow-up of a randomised controlled trial

Abstract: Objective To examine the quality of life experienced by women with symptomatic uterine fibroids who had been treated with UAE in comparison to myomectomy. We report the four-year follow-up of the FEMME randomised trial. Two-year follow-up data has been previously reported. Study Design Premenopausal women who had symptomatic uterine fibroids amenable to myomectomy or uterine artery embolization were recruited from 29 UK hospitals. Women were excluded if they had signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…The health‐related QOL score at 2 years of follow‐up was the primary time point. The data have been reported elsewhere 17,19 . The primary analyses were by ITT.…”
Section: Methodsmentioning
confidence: 99%
“…The health‐related QOL score at 2 years of follow‐up was the primary time point. The data have been reported elsewhere 17,19 . The primary analyses were by ITT.…”
Section: Methodsmentioning
confidence: 99%
“…Following our literature search and applying our exclusion criteria, a total of 17 studies were included for further analysis, which are summarised in Table 2 (Mara et al 2008 ; Daniels et al 2021 ; Holub et al 2008 ; Mara et al 2012 ; McLucas et al 2001 ; Pron et al 2005 ; Kim et al 2008 ; Pinto Pabón et al 2008 ; McLucas 2013 ; Pisco et al 2017 ; Torre et al 2017 ; Walker and McDowell 2006 ; Hirst et al 2008 ; Bonduki et al 2011 ; Serres-Cousine et al 2021 ; Ravina et al 2000 ; Firouznia et al 2009 ; Redecha Jr et al 2013 ). Our analysis found a mean pregnancy rate of 39.4%, live birth rate of 69.2% and miscarriage rate of 22% (Table 2 ).…”
Section: Uae and Fertilitymentioning
confidence: 99%
“…Of the studies included in the analysis there were two RCTs which compared outcomes following UAE and myomectomy (Mara et al 2008 ; Daniels et al 2021 ). Mara et al ( 2008 ) found pregnancy rates of 50% in the UAE cohort (26 patients) compared to 78% in the myomectomy (either open or laparoscopic) cohort (40 patients).…”
Section: Uae and Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…UAE offers several advantages in comparison to surgical options (myomectomy or hysterectomy), including shorter average length of hospital stay, shorter recovery period, similar rates of symptomatic improvement, retention of the uterus, and no requirement for general anaesthesia [1][2][3][4][5][6][7][8][9]. However, UAE has slightly higher rates of long-term reintervention compared to hysterectomy [1][2][3][4][5][6][7][8][9], and a recent randomised controlled trial suggested that myomectomy may provide better symptomatic improvement after 2 years, but likely not at 4 years [13,14]. While UAE is a safe and low-risk procedure, infective complications do occur, which may require hysterectomy (0.4-0.7%) if not resolved with intravenous (IV) antibiotics alone [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%